Promoting the Use of E-books by the Use of Electronic Enrichment - Gethin, Peter (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Since the arrival of the Internet and, so called „ dot com” companies embarking upon e-commerce on the information super highway, we now see books being sold online. Dot com companies setting out to sell books online have to achieve the same result as the conventional bookshop. It is not surprising, therefore, that they have also begun to develop techniques to promote the sale of books in their particular environment.